新型拖拉机齿轮浮动式锻模设计 - 于金伟 (Jixie chuandong)
The problems in the former forging die of tractor driven cylindrical gears are discussed,a new typed structure of the forging die is proposed,with a float mould core and a float concave die,forging is formed within a closed ring cavity,the forged parts have no burrs,and the spare material is reduced by 80%,the material consumption and the production cost is greatly decreased.